Stereo-chemical contributions to the glass transition and liquid–liquid phase separation in high molecular weight poly(N-vinyl carbazole). Issue 35 (21st March 2016) - Al Lafi, Abdul G.; Hay, James N.
Abstract : Thermal history and purification effects on the structural properties of PVK were investigated. Liquid–liquid phase separation is suggested to occur by separation of isotactic rich segments from a matrix which is predominantly atactic. Abstract : The effects of thermal history and purification on poly( N -vinyl carbazole) (PVK) was investigated focusing on thermal, dielectric and structural analyses. A single glass transition temperature, T g at 225 °C was observed in the case of the material as received, while two distinct T g s were identified in the purified samples. Thermal annealing at a temperature above 275 °C also introduced a transition identical to that observed on purification. The nature of the two transitions was confirmed to be that of α-transitions having activation enthalpies of 400 ± 50 kJ mol −1 as determined by dielectric relaxation spectroscopy. No change in molecular weight was observed and 1 H-NMR spectroscopy showed that there was little or no change in tacticity as a result of these treatments. It is suggested that liquid–liquid phase separation occurs by separation of isotactic rich segments from a matrix which is predominantly atactic, as indicated by the T g temperature. It is considered that the liquid–liquid phase separation was driven by the differences in solubility of two stereo-isomers. This mechanism is preferred to that of phase separation by molecular weight driven by the higher molecular weight phase forming a liquid crystalline structure since the observed T g s at 196, 215 and 225 °C have differences too great to be accounted for by changes in molecular weight alone but consistent with the known T g values of the stereoregular polymers.